2010
DOI: 10.1016/j.japwor.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of production networks in East Asia: Duration and survival of trade

Abstract: This paper sheds light on the stability of international production networks in East Asia from the perspective of the duration and survival of bilateral trade relationships at the product-line level. Using highly disaggregated data for intra-East Asian machinery trade, survival analysis is conducted as well as the examinations of the duration and volatility of trade relationships. The product-level analyses reveal that, compared to machinery finished products, machinery parts & components are traded through lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 14 publications
(14 reference statements)
4
54
0
1
Order By: Relevance
“…lasted longer, and so did exportsof machinery, a finding confirmed by the analysis of Asian trade flows by Obashi (2010). explore the determinants of export survival further by testing the implications of a search model proposed by Rauch and Watson (2003) in which importers search for low-cost suppliers and exporters invest optimally in production capacity in the face of moral hazard (risk of non-payment).…”
Section: Introductionmentioning
confidence: 86%
“…lasted longer, and so did exportsof machinery, a finding confirmed by the analysis of Asian trade flows by Obashi (2010). explore the determinants of export survival further by testing the implications of a search model proposed by Rauch and Watson (2003) in which importers search for low-cost suppliers and exporters invest optimally in production capacity in the face of moral hazard (risk of non-payment).…”
Section: Introductionmentioning
confidence: 86%
“…Hence transactions within these networks tend to be stable. Obashi (2010aObashi ( , 2010b found that trade in parts and components between East Asian countries tends to be more resilient than trade in finished goods or trade with extra-regional partners. Thus, while the Asian Crisis reduced the locational advantages of channeling FDI to ASEAN, it did not cause the MNEs to break off existing relationships with Southeast Asian firms.…”
Section: Fdi In East Asia From 1985-2011mentioning
confidence: 99%
“…Basically, this study employed a gravity model in order to evaluate the relationship between two trading partners that are located far away, in this case Malaysia and each MEAC country. As the previous studies found, distance has a negative impact on exports (Obashi 2010). The longer the distance between trade partners, the higher the costs (transportation costs) that will result and indirectly lower the profit margin.…”
Section: Gravity Modelmentioning
confidence: 66%
“…Empirically, the gravity model, which was employed by many previous studies, was found to be powerful (Obashi 2010). Gravity models have strong power in explaining the trade pattern and testing hypotheses as the aim of the empirical part of using gravity models is to test the hypothesis concerning the bilateral trade flows of Malaysia and candidate countries (Middle Eastern Asian countries).…”
Section: Gravity Modelmentioning
confidence: 99%